Vitamin B12 Supplementation: Preventing Onset and Improving Prognosis of Depression - Sangle, Prerna (Cureus, 2020)
Depression is a common mental health condition occurring across all ages, genders, and populations and is almost always multifaceted. It can manifest as a form of metabolic disorder, endocrine disorder, cardiovascular diseases, inflammatory disorders, deficiencies, or neurodegenerative disorders. Although there have been various treatment options available for the treatment of depression, it is still a sizable global health concern requiring more attention. This review article was produced by researching data and studies to prove a relationship between Vitamin B12 and depression. Numerous studies were reviewed, and based on these studies, it was concluded that supplementation of Vitamin B12 early enough can delay the onset of depression and improve the effect of anti-depressants when used in conjunction with Vitamin B12. Although other vitamins like Vitamin B6 and folate are known to have an impact on depression, we have primarily focused on Vitamin B12 in an attempt to offer the providers a foundation to address this concern with their patients prone to depression or have had a major depressive episode in their life.